2003
DOI: 10.1088/1367-2630/5/1/301
|View full text |Cite
|
Sign up to set email alerts
|

Antihelium-3 production in lead-lead collisions at 158AGeV/c

Abstract: Abstract. The NA52 experiment measured particle and antiparticle yields at 0 • production angle over a wide range in rapidity in lead-lead (Pb-Pb) collisions at 158 A GeV/c with a minimum bias trigger. Besides O(10 6 ) antiprotons (p) and O(10 3 ) antideuterons (d) a total of five antihelium-3 ( 3 He) were found. The resulting invariant differential 3 He production cross sections at p t 0 GeV/c turn out to be E d 3 σ dp 3 = (2.5 ± 1.8) × 10 −7 bc 3 GeV −2 at a rapidity of y = 3.4 in the laboratory system and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(13 citation statements)
references
References 23 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…It was further used as the model applied to data obtained at the Alternate Gradient Synchrotron (AGS) at Brookhaven National Laboratory (BNL) where several different experiments (E802/E866, E814, E864, E877, E878) have results on the production of light nuclei [68,69,70]. Furthermore, at the CERN SPS it was used for the interpretation of heavy-ion data at three different experiments (NA44, NA49, NA52) [71,72,73,74,75,76,77,78,79,80,81,82,83]. The model was also successfully applied to describe the yields of nuclei at RHIC [84,85,86,87,88,89,90].…”
Section: Coalescence Modelmentioning
confidence: 99%
“…It was further used as the model applied to data obtained at the Alternate Gradient Synchrotron (AGS) at Brookhaven National Laboratory (BNL) where several different experiments (E802/E866, E814, E864, E877, E878) have results on the production of light nuclei [68,69,70]. Furthermore, at the CERN SPS it was used for the interpretation of heavy-ion data at three different experiments (NA44, NA49, NA52) [71,72,73,74,75,76,77,78,79,80,81,82,83]. The model was also successfully applied to describe the yields of nuclei at RHIC [84,85,86,87,88,89,90].…”
Section: Coalescence Modelmentioning
confidence: 99%
“…Deuterons and antideuterons are copiously produced in heavy-ion collisions [1][2][3][4][5][6][7][8][9][10][11], but less abundantly in lighter particle collisions, such as pp [12,13] and pp [14] collisions, photoproduction γp [15], and e + e − annihilation at ϒ(nS) [16] and Z 0 [17] energies. Measurements of heavier antinuclei, such as antitritons and 3 He nuclei, have only been reported in pA [18,19] and AA collisions [11,[20][21][22][23]. The high luminosity provided by the LHC allows these measurements to be extended to higher energies and transverse momenta (p T ) than in previous experiments, and provides in addition the possibility to detect for the first time antinuclei heavier than antideuterons in pp collisions.…”
Section: Introductionmentioning
confidence: 99%
“…APCP is known as the fourth state of matter, which consists of free charged ions and radicals moving in random directions. Although APCP has been extensively applied to the inactivation of liquid-borne or surface-borne agents (25)(26)(27)(28)(29)(30), only a few inactivation studies exposing airborne microbial agents to APCP have been conducted (31)(32)(33)(34). A recent study reported that a significant fraction (Ͼ85%) of airborne bacteria and fungi from both indoor and outdoor environments lost their viability within 60 ms of exposure to APCP (34).…”
mentioning
confidence: 99%